KEANEKARAGAMAN BELALANG (ORTHOPTERA : CAELIFERA) PADA AREA PERSAWAHAN DI DESA SEKETI, KECAMATAN MOJOAGUNG, KABUPATEN JOMBANG - Nur Qomariyah Pratiwi; Saiful Bahri; Saiku Rokhim; Ita Ainun Jariyah; Esti Tyastirin (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
Rice field ecosystem is an artificial ecosystem that is used in agriculture. Rice fields in Seketi Village have vegetation types of corn, sugar cane, and rice, so that it will affect of grasshopper diversity in each vegetation. The purpose of this study was to determine the diversity of grasshoppers (Caelifera) and to determine the effect of vegetation on the diversity of grasshoppers in the rice fields of Seketi Village. The method used is purposive sampling and direct capture, namely research by making 5 plots measuring 5m x 5m with different types of plant vegetation (paddy, corn, sugar cane) catching with Sweep Net (insect nets). The results showed that there were species of Phlaeoba antennata, Phlaeoba fomusa, Oxya chinensis, Valanga nigricornis, Caryanda spuria, Atractomorpha crenulata, and Tettigidea sp. with a total of 152 individuals from 3 families. The diversity index value shows that plot 4 (maize plants) has the highest H' = 1.58 with 6 species of grasshoppers found and plot 1 (cane plants) has the lowest diversity index value of H = 1.09. Based on the differences in the value of grasshopper diversity in each plot caused by different types of vegetation, habitat conditions, and abiotic factors.